Antihyperglycemic Activity of Aqueous Extract of Insulin Leaves (Tithonia diversifolia) on Hyperglycemic Rats (Rattus norvegicus) - Anisa Rachma Sari; Tyas Rini Saraswati; Enny Yusuf Wachidah Yuniwarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Insulin leave (Tithonia diversifolia (Hemsl.) A. Gray) empirically used by people as antihyperglycemic drugs. The study was aimed to evaluate antihyperglycemic activity as well as to determine the most optimum dose of T. diversifolia to reduce blood glucose levels. Hyperglycemic condition was induced to male Rattus norvegicus rats by intraperitoneal injection of alloxan at a dose of 150 mg/kg bw (body weight). In this study, completely randomized design was performed with three treatment groups and five times repetition. Group P1 received glibenclamide 10 mg/kg bw, P2 received aqueous extract of T. diversifolia at a dose of 150 mg/kg bw, P3 received aqueous extract of T. diversifolia at a dose of 300 mg/kg bw. Administration of both glibenclamide and aqueous extract of T. diversifolia was conducted orally for 28 days. Data were analyzed using Anova and Duncanâ€™s test with 95% confidence level (Î± = 0.05). The results showed that the mean percentage of decrease in blood glucose levels, drink intake and body weight of all treatment groups were not significantly different (p0.05). Data of feed intake showed that P1 was significantly different from P2 (p0.05), but P2 was not significantly different from P3 (p0.05). Based on the result of this research, it was found that the low doses of aqueous extract of T. diversifolia has the same ability to decrease blood glucose level compared to glibenclamide. Futhermore, this study provide some information that can be used as preclinical analysis to determine effective doses of aqueous extract of T. diversifolia to decrease blood glucose levels.Â Â